(untitled) (Journal of Information Systems and Technology Management, 2009)
The objective of this paper is to analyze the resistance factors experienced by employees of an electronics manufacturing plant located in the region of Campinas (SP), following the implementation of an information technology (IT) project. The substantive contribution to literature that this paper offers consists of the description of relationships among resistance factors and firm characteristics in order to support propositions of approaches that could ease acceptance to new information systems, thus reducing employee's resistance. Results suggest that a set of factors, such as management of the employee's expectations and perception of power redistribution, are positively related to resistance to its acceptance. In the final section, recommendations for future research are presented.